1996
DOI: 10.1210/endo.137.10.8828509
|View full text |Cite
|
Sign up to set email alerts
|

Androgens markedly stimulate the accumulation of neutral lipids in the human prostatic adenocarcinoma cell line LNCaP.

Abstract: Microscopic evaluation of LNCaP cells stained with the lipophilic dye Oil red O revealed that androgens induce a marked stimulation of lipid droplet accumulation. As determined by quantitative analysis of the Oil red O extracted from the stained cells, stimulatory effects of the synthetic androgen R1881 became apparent at concentrations as low as 10(-11) M. Maximal induction (15-fold) was reached at 10(-8) M. Increases were observed 2 days after hormone addition and were maximal 1 day later. Accumulation of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1
8

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 17 publications
5
77
1
8
Order By: Relevance
“…Finally, lipid metabolism is highly regulated by androgens in prostate cancer cells (Swinnen et al 2004). Bicalutamide inhibits lipid synthesis in LNCaP cells (Swinnen et al 1996), and increased levels of key lipogenic enzymes have been reported in CRPC patients (Rossi et al 2003, Ettinger et al 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, lipid metabolism is highly regulated by androgens in prostate cancer cells (Swinnen et al 2004). Bicalutamide inhibits lipid synthesis in LNCaP cells (Swinnen et al 1996), and increased levels of key lipogenic enzymes have been reported in CRPC patients (Rossi et al 2003, Ettinger et al 2004.…”
Section: Discussionmentioning
confidence: 99%
“…In the normal prostate, this anabolic action is essential to maintain the secretory function of the prostate gland required for optimal male fertility. In the case of tumor cells, we observed in 1996 that exposure of LNCaP prostate cells to natural or synthetic androgens leads to a marked accumulation of lipid droplets in the cytoplasm, largely via increased synthesis of fatty acids and cholesterol (Swinnen et al 1996). Importantly, this lipogenesis was reversed by an AR antagonist and was not observed in AR-negative prostate cancer cells.…”
Section: Lipid Metabolism Is Androgen-regulated In Prostate Cancermentioning
confidence: 99%
“…Hager et al initially investigated the role of cholesterol metabolism in prostate cancer and found that during early stage development, large accumulations of membrane associated lipids developed [4]. Furthermore, Swinnen et al [7] correlated androgen stimulation in prostate cancer cells with the accumulation of neutral lipids (triglyceride and cholesterol esters). Sonn et al [8] discovered that exogenous fat intake has also been correlated with prostate cancer mortality and serum androgen levels.…”
Section: Introductionmentioning
confidence: 99%
“…Upon synthetic androgen (R1881) stimulation of cells, Heemers et al verified an increase in expression of SCAP and SREBPs within the nucleus [17]. This increase in expression did not occur in androgenunresponsive cells and thus this process is believed to be androgen dependent in nature [7].…”
Section: Introductionmentioning
confidence: 99%